A VISUAL AND VERBAL ANALYSIS OF CHILDREN REPRESENTATION IN TELEVISION ADVERTISEMENT - Budi Hermawan; Elka Zenereshynta Nuvra Ardhernas (English Review: Journal of English Education, 2014)
Abstract: The study investigates the representation of children in television advertisement of 3 Indie+ cellular phone operator. The study is descriptive qualitative and has employed Kress Leuweenâ€™s Reading Images (2006) to analyze the visual data, and Hallidayâ€™ Transitivity System (1994, 2004) which is simplified by Gerot and Wignell (1995) for the analyzing the verbal data. The aim of the study is to examine the representation of children visually and verbally in the 3 Indie+ cellular phone operator advertisement. Based on the data analysis, the study finds that visually children are represented as a naive person who is â€œpretending to knowâ€ adult life when in fact they are still a child through the use of setting, layout composition, and perspective (shot, gaze). Children are verbally represented through the use of mental and material processes as somebody who tells about their hope, obsession, and aspirations in the future, and their naive imaginations of how an adult life is In relation to the product advertised the representation signifies that unlike other providers, using 3 Indie+ is very easy; it is not as hard as to live as adults.Keywords: advertisement, cellular phone, representation, semiotic, text, and visual grammar.